Hubungan antara pemberian makanan pendamping air susu ibu dengan status gizi anak 6-24 bulan - Igir, Anggun; Punuh, Maureen Irinne; Malonda, Nancy Swanida Henriette (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Malnutrition can lead to physical and mental retardation, decreased thinking ability, and increased productivity, as well as increasing the risk of disease and death in children. Malnutrition can be caused by inappropriate provision of complementary foods to meet children's nutritional needs. Purpose: To determine the relationship between complementary feeding and breast milk and the nutritional status of children aged 6-24 months. Method: This was an observational analytical study with a cross-sectional design. The population was 363 children aged 6-24 months, with a total sample size of 86 children. The sampling technique used was a probability sampling with simple random sampling. The instrument used in this study was the Child Feeding Questionnaire (CFQ) to measure the criteria for complementary feeding. Results: Based on the weight-for-age (W/A) index, 86.0% had normal weight and 11.6% were underweight. Based on the weight-for-height (W/B) index, 84.9% were categorized as well-nourished, and 10.5% were malnourished. In this study, the appropriate provision of complementary feeding was 88.4%, while the inappropriate provision was 11.6%. The bivariate analysis, based on the weight-for-age (W/A) and weight-for-height (W/H) indices, yielded a p-value of 0.000 (p<0.05). This indicates a relationship between the provision of complementary foods and breast milk and the nutritional status of children aged 6-24 months. Conclusion: There is a relationship between the provision of complementary foods and breast milk and the nutritional status of children aged 6-24 months. Suggestion: Complementary foods should be provided according to the child's age, starting with mashed, soft/finely chopped complementary foods, and continuing with family meals. Complementary foods should also include a variety of ingredients, such as carbohydrates, animal protein, vegetable protein, fruits, and vegetables, and hygiene should be maintained during the preparation and serving of complementary foods. Keywords: Children; Complementary Foods; Nutritional Status. Pendahuluan: Kekurangan gizi dapat menyebabkan hambatan fisik, mental, penurunan kemampuan berpikir, produktivitas, serta meningkatkan risiko penyakit dan kematian anak. Penyebab kekurangan gizi dapat disebabkan oleh pemberian MP-ASI yang tidak tepat dengan kebutuhan gizi anak. Tujuan: Untuk mengetahui hubungan antara pemberian makanan pendamping air susu ibu dengan status gizi anak 6-24 bulan. Metode: Penelitian observasional analitik dengan desain cross sectional study. Populasi dalam penelitian ini adalah 363 anak berusia 6-24 bulan dengan total sampel berjumlah 86 anak, teknik pengambilan sampel menggunakan probability sampel dengan metode simple random sampling. Instrumen yang digunakan dalam penelitian ini yaitu Child Feeding Questionnaire (CFQ) untuk mengukur kriteria MP-ASI. Hasil: Berdasarkan pengukuran indeks BB/U, terdapat 86.0% dengan berat badan normal dan sejumlah 11.6% dengan berat badan kurang. Berdasarkan pengukuran indeks BB/PB terdapat 84.9% dengan kategori gizi baik dan terdapat 10.5% mengalami gizi kurang. Pada penelitian ini, kategori pemberian MP-ASI tepat sejumlah 88.4% dan kategori MP-ASI tidak tepat sejumlah 11.6%. Hasil analisis bivariat berdasarkan indeks BB/U dan BB/PB diperoleh p-value 0.000 (p<0.05). Hal ini menunjukkan terdapat hubungan antara pemberian makanan pendamping air susu ibu dengan status gizi anak 6-24 bulan. Simpulan: Terdapat hubungan antara pemberian makanan pendamping air susu ibu dengan status gizi anak 6-24 bulan. Saran: MP-ASI perlu diberikan sesuai dengan usia anak, dimulai dari MP-ASI dengan bentuk lumat, lembek/dicincang halus hingga makanan keluarga. Pemberian MP-ASI juga harus beragam jenis bahan makanan, seperti karbohidrat, protein hewani, protein nabati, buah dan sayur serta harus menjaga kebersihan dalam proses pengolahan dan penyajian MP-ASI. Kata Kunci: Anak; Makanan Pendamping Air Susu Ibu (MP-ASI); Status Gizi.